Biological control agents: mechanisms of action, selection, formulation and challenges in agriculture - Villavicencio-Vásquez, Mirian; Espinoza-Lozano, Fernando; Espinoza-Lozano, Lisbeth; Coronel-León, Jonathan (Frontiers in Agronomy, 2025)
The increasing global population has intensified the demand for food production, both in quantity and quality. To meet this challenge and prevent crop diseases, chemical pesticides have been widely used. However, their negative effects on human health and the environment have driven the search for sustainable alternatives. In this context, microbial-based biopesticides, particularly Trichoderma and Bacillus, have emerged as key biocontrol agents in agroecosystems. This review provides a comprehensive overview of their agricultural significance, focusing on their mechanisms of action, efficacy, and biotechnological advancements aimed at optimizing their performance. Trichoderma spp. act primarily through mycoparasitism, nutrient competition, and antibiosis, while Bacillus spp. employ mechanisms such as lipopeptide production, lytic enzymes, siderophores, and the activation of induced systemic resistance (ISR). Unlike traditional reviews that primarily describe their biological functions, this work offers a structured framework for their application, addressing key factors such as selection criteria for effective biocontrol agents, formulation strategies, product stability, viability, and regulatory challenges in commercial agriculture. Additionally, recent studies on genetic enhancement, including CRISPR-based modifications, are examined to improve their adaptability, metabolic activity, and effectiveness in pathogen control across diverse agricultural systems. By integrating biological, technological, and practical perspectives, this review aims to bridge the gap between scientific advancements and real-world agricultural applications, contributing to the development of scalable and sustainable disease management strategies.